Efficacy of Oral Mini Pulse Betamethasone in the Treatment of Vitiligo (Bangladesh Medical Journal, 2014)
Vitiligo is a multifactorial polygenic disorder with a complex pathogenesis, characterized by depigmented macules in skin. A clinical trial was conducted to evaluate the efficacy of oral mini pluse betamethasone in the treatment of vitiligo patients. The study was done in the department of Dermatology and Venerology, Bangabandhu Sheikh Mujjb Medical University, Dhaka, Bangladesh for duration of July 2009 to June 2010. Among thirty patients of vitiligo, most of the male patients (60%) and most of the femal patients (73%) were between 20 to 25 years. Majority of patients (70%) had been suffering from vitiligo for less than 3 years and 53% patients had family history. Twenty one (70%) patients had acro-facial type vitiligo and 23(76.7%) cases were progressive in nature. In this study, response was slight in 33.33%, moderate in 26.67% marked in 33.33% and excellent in 6.67% of cases after 12 weeks. Twenty percent (20%) of total patients were seen to be with clinical side effect. Among the side effects, weight gain 2(6.67%), and acene 2(2.67%) was most prevalent, others include general weakness 1(3.33%) and mild headache 1(3.33%). In conclusion, oral mini pulse betamethasone seems to be an effective treatment modality to arrest the progression of vitiligo and induction of repigmentation. DOI: http://dx.doi.org/10.3329/bmj.v40i3.18675 Bangladesh Medical Journal 2011 Vol.40(3):44-47